2017
DOI: 10.1093/bja/aew463
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative oral fluid intake in paediatric day case surgery influences the need for opioids and postoperative vomiting: a controlled randomized trial

Abstract: NCT02288650.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 30 publications
2
34
0
6
Order By: Relevance
“…Furthermore, although sedative premedications were consistently effective in reducing preoperative anxiety, effects of them on the postoperative behavioral alteration is debatable . Although no previous study evaluated interaction between preoperative fasting and ED in this setting, Xará et al in 2013 reported that prolonged preoperative fasting is a risk factor for postoperative emergence along with postoperative pain and major surgery and Chauvin et al also reported that thirst might be a reason for unsettling behavior in children in the postoperative period. A number of studies have reported a significantly longer duration of fasting than recommended by the various society guidelines…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, although sedative premedications were consistently effective in reducing preoperative anxiety, effects of them on the postoperative behavioral alteration is debatable . Although no previous study evaluated interaction between preoperative fasting and ED in this setting, Xará et al in 2013 reported that prolonged preoperative fasting is a risk factor for postoperative emergence along with postoperative pain and major surgery and Chauvin et al also reported that thirst might be a reason for unsettling behavior in children in the postoperative period. A number of studies have reported a significantly longer duration of fasting than recommended by the various society guidelines…”
Section: Discussionmentioning
confidence: 99%
“…This can have an impact in the postoperative outcome in the form of emergence delirium (ED). Recently, a randomized controlled trial reported that early postoperative oral fluid intake reduced need of postoperative opioid and postoperative vomiting . Young children does not tolerate fasting as well as adults, as they have a higher glucose requirement, and a minority of young children become hypoglycemic by the time of induction of anesthesia .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eltern müssen dazu motiviert werden, ihr Kind zu umarmen und zu streicheln [16], denn es ist nicht selten zu beobachten, dass diese eher passiv "dabeisitzen" und mehr die Szene beobachten als mit dem Kind zu interagieren. Ebenfalls schon unmittelbar nach der OP im Aufwachraum sollten Kinder etwas Süßes trinken können, denn dadurch können der Bedarf an Opioiden und die Rate an Erbrechen gesenkt werden [17].…”
Section: Merkeunclassified
“…Neuere Untersuchungen haben gezeigt, dass die metabolische und hämodynamische Situation nach Narkoseeinleitung bei kleinen Kindern durch optimierte präoperative Nüchternzeiten verbessert wird [5] und dass Kinder weniger Opioide brauchen und seltener erbrechen, wenn sie auch postoperativ schnell wieder trinken dürfen [6].…”
Section: Robert Sümpelmannunclassified